The Easy and Early Diagnosis of Typhoid Fever - Kinikar Anagha; Bhalerao Deepika; Roushani Shahriar; Kulkarni Sanjeev (Journal of Clinical and Diagnostic Research, 2012)
Background and Objective: Typhoid fever is endemic in India. Its diagnosis is usually confirmed by blood culture, clot culture, stool culture and the Widal agglutination test. In the present study, we assessed the usefulness of the Enterocheck WB test in detecting the IgM antibodies in typhoid fever. Materials and Methods: A total of 83 cases of clinically suspected typhoid fever were included in the study. A blood culture and the Widal test were done by using the standard methods. The Enterocheck WB test was done according to the manufacturer’s instructions. Results: Of the 83 cases, the blood culture was positive for Salmonella typhi in 19 (22.89%) cases, among which the Widal test was positive in 12 (14.45%) cases and the Enterocheck WB test was positive in 17 (20.48%) cases. The sensitivity & specificity of the Enterocheck WB test were found to be 89.47% and 96.87% respectively. Interpretation and Conclusion: We compared the sensitivity and the specificity of the Enterocheck WB test and the Widal test to those of the blood culture as the gold standard method in the diagnosis of typhoid fever. We found that the Enterocheck WB test for the detection of the IgM antibodies was easy to perform and that no special equipment or prior training of the paramedical staff were required for the testing and the interpretation of the results. Hence, it can be concluded that the Enterocheck WB test can be used as a complimentary test as compared to the blood culture and the Widal test for the diagnosis of typhoid fever.